FIGUR PENDIDIK HUMANIS DI MASA PANDEMI COVID 19 - Asfiati Asfiati; Ihwanuddin Pulungan (IAIN Padangsidimpuan, 2020)
The Covid 19 pandemic has shifted the learning process, which was originally running in real terms, now to the virtual world. All hopes that the Covid 19 pandemic period is used to create added value in seeing humans based on moral values (ethics) of religious humanism (religious humanism). Likewise, emulating humanist educator figures during the Covid 19 pandemic. Humanist educators guide students to think positively. Learning that is faced with many applications, via Facebook, Youtube, IG, WA, Line, Zoom, Microsoft Team, Google Classroom, or communication via teleconference seems to give rise to creativity. Humanist educators present their respective roles well so that learning becomes fun and still results in progress.Â Â